Superior Performance of Fe(BTC) With Respect to Other Metal‐Containing Solids in the N‐Hydroxyphthalimide‐Promoted Heterogeneous Aerobic Oxidation of Cycloalkanes. Issue 7 (7th March 2013) - Mikami, Yusuke; Dhakshinamoorthy, Amarajothi; Alvaro, Mercedes; Garcia, Hermenegildo
Abstract A series of heterogeneous catalysts incorporating N‐hydroxyphthalimide (NHPI) and containing transition‐metal ion as promoter (Fe3+ or Co2+) on a support such as Fe(BTC) (BTC=1, 3, 5‐benzenetricarboxylate), zeolites Y and Beta, mesoporous Al‐MCM‐41 aluminosilicate, and nonporous silica have been prepared and tested for the aerobic oxidation of cyclooctane. It was found that NHPI/Fe(BTC) as catalyst exhibits the best performance in the series with the highest selectivity to the ‐ol/‐one mixture at identical conversions. These results have been interpreted as being due to the appropriate combination between reaction cavity dimensions and confinement of the autooxidation chain reaction. The catalytic activity for cyclohexane using NHPI/Fe(BTC) under similar reaction conditions is also reported.